2017
DOI: 10.18203/2349-3291.ijcp20174730
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hypertension in urban school children aged 5 to 10 years in North India

Abstract: Background: Blood pressure in children is a known predictor cardiovascular health and outcome in adulthood. Prevalence of hypertension in Indian adults is rising over the years. It is anticipated that the blood pressure in Indian children might have also increased over the years. This study was undertaken to document the prevalence of hypertension among urban school children aged 5-10 years in North India. Methods: This cross-sectional study was undertaken in 28 private schools in urban Faridabad, Haryana. A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…More specefically, the prevalence of HTN among under weight was 14.6% compared to 20.6% among normal weight persons. [ 15 ] In a cross-sectional study in northern India among 1,085 school children aged from 11 to 17 years, the prevalence of HTN and overweight were 5.9% and 3.5%, respectively. [ 16 ] However, Sumboonnanonda et al .…”
Section: Discussionmentioning
confidence: 99%
“…More specefically, the prevalence of HTN among under weight was 14.6% compared to 20.6% among normal weight persons. [ 15 ] In a cross-sectional study in northern India among 1,085 school children aged from 11 to 17 years, the prevalence of HTN and overweight were 5.9% and 3.5%, respectively. [ 16 ] However, Sumboonnanonda et al .…”
Section: Discussionmentioning
confidence: 99%
“…Similar prevalence of hypertension was reported in studies conducted by Sharma et al, Sundar et al and Das et al (20.0%, 21.5% and 19.7% respectively). [13][14][15] The prevalence of pre-hypertension was found to be 28.65%. Similarly Nagar et al reported 30.2% prevalence of pre-hypertension among School Going Adolescents in Surendranagar City, Gujrat.…”
Section: Discussionmentioning
confidence: 98%
“…This is consistent with previous studies that reported the value of systolic blood pressure, diastolic blood pressure, mean arterial pressure and pulse pressure were higher with an increase in body mass index, but not with weight gain. [27][28][29] Das et al 30 reported that an increase in age and BMI status increases the prevalence of hypertension in boys and girls. Al-Bachir et al 31 reported that obese adolescents have more abdominal fat associated with alteration factors affecting cardiometabolic such as an increase in LDL, triglycerides and blood pressure which in turn will lead to the risk of cardiovascular disease.…”
Section: Obesity and Occurrence Of Hypertensionmentioning
confidence: 99%